Preparation of Electrochemical Sensor Based on Zinc Oxide Nanoparticles for Simultaneous Determination of AA, DA, and UA - Pan, Yuanzhi; Zuo, Junli; Hou, Zhongyu; Huang, Yizhong; Huang, Cancan (Frontiers in Chemistry, 2020)
ZnO nanoparticles (NPs) were synthesized using a hydrothermal method. Scanning electron microscope (SEM) and X-ray diffraction have been used for characterizing the synthesized ZnO NPs. An electrochemical sensor was fabricated using ZnO NPs–modified glassy carbon electrode for simultaneous determination of ascorbic acid (AA), dopamine (DA), and uric acid (UA). The proposed electrochemical sensor exhibited excellent detection performance toward three analytes, demonstrating that it can potentially be applied in clinical applications. The results indicated the ZnO NPs–modified electrode can detect AA in the concentrations range between 50 and 1,000 μM. The ZnO NPs–modified electrode can detect DA in the concentrations range between 2 and 150 μM. The ZnO NPs–modified electrode can detect UA in the concentrations range between 0.2 and 150 μM. The limits of detections of AA, DA, and UA using ZnO NPs–modified electrode were calculated to be 18.4, 0.75, and 0.11 μM, respectively.